The identification of emotions from gait. Issue 5 (September 2016) - Birch, Ivan; Birch, Tabitha; Bray, Diane
Highlights: Anecdotal evidence suggests the possibility of identifying emotions from gait. 30 untrained analysts viewed video footage of 6 walkers displaying 5 emotions. Analysts correctly identified all 5 emotions significantly better than by chance. The possible effects of emotion on gait should be considered during gait analysis. The results have implications for forensic psychology, and court room procedures.